ANALYTICAL STUDY OF THE POLITICAL INSTABILITY AND ITS IMPACTS ON DEMOCRACY IN PAKISTAN - Dr. Aisha Ahmad; Fazeel Ashraf Qaisrani; Dr. Nida Fatima; Iqra Nazeer Malghani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Political instability has harmful effects on any state, but in developing or underdeveloped countries, political instability is a threat to security. Therefore, Political stability is considered very important in the progress of any countries while in the under developing countries of the third world commonly face political insecurity, which has become a severe and frightening problem. Due to political insecurity in these countries creating huge problems and hindering the development. The matter of this article revolves around the problem of political stability in framework of identity and ability crisis in Pakistan. Political stability plays an important role in keeping society integrated and in maintaining legitimacy within the state. It is a prerequisite for the economic development, social integration, and supremacy of law in a state. The stability of political system has direct effects on the processes of nation and state building. These both require stable political systems for their growth and flourishing. The development of nation and state without firm and organized system of politics is not possible and government becomes only a tug of war amongst various interest groups. In sum, article endeavors to explore the possible causes and effects of political instability in Pakistan.